Identification of phylogenetic relationship and polyembryony trait in F1 hybrid offspring of Kiyomi and Egan No.1 - SONG Fang; YANG Linxin; WANG Ce; JIANG Yingchun; HE Ligang; WANG Zhijing; MA Xiaofang; ZHANG Yu; SONG Xin; WU Liming (Guoshu xuebao)
[Objective] Citrus is the largest fruit crop in the world and one of the most important economic crops in Southern China. Crossbreeding is one of the most effective methods for developing new citrus varieties. The use of molecular marker-assisted breeding has become one of the most effective ways to identify the genetic relationships of citrus. Polyembryony is a unique biological phenomenon in citrus plants and has been proven to be a dominant trait controlled by a single gene. The aim of this study was to utilize molecular marker detection technology for rapid and simple hybrid verification and polyembryony detection in the hybrid offspring of Kiyomi × Egan No.1, in order to provide germplasm resources for the breeding of new citrus varieties. [Methods] In this study, 130 Kiyomi (Citrus unshiu Marc. × C. sinesis Osbeck) × Egan No.1 (C. reticulata Blanc.‘Ponkan’) hybrid offspring were utilized as materials. The SSR molecular markers were employed to identify the relationship between the 130 hybrid offspring and two parents, Kiyomi and Egan No.1. Two pairs of primers, mite_p1 and mite_p2, which can identify citrus polyembryony traits, were used to differentiate the monoembryonic and polyembryonic traits of the hybrid offspring. Among these 130 hybrid offspring, 44 offspring were fruit-bearing. The seeds of these 44 fruit-bearing hybrid offspring were collected for validation of the polyembryony molecular marker detection results. [Results] The primer CHR2-2 identified 103 hybrid offspring with amplification of distinct parental bands, achieving a hybrid identification rate of 79.23%. The primer CHR8-3 identified 69 hybrid offspring with distinct parental bands, with a hybrid identification rate of 53.08%. The primer CHR8-4 identified 68 hybrid offspring with distinct parental bands, resulting in a hybrid identification rate of 52.31%. The comprehensive hybrid identification rate reached 99.23%. Using the NTSYSpc-2.10e software and the unweighted pair group method with arithmetic average (UPGMA), the similarity coefficients of all the hybrid offspring were obtained, ranging from 0.805 to 0.99, indicating relatively high genetic similarity among the offspring. The hybrid offsprings in the largest cluster had a closer genetic relationship with the maternal parent Kiyomi, consisting of 45 offsprings, accounting for 34.62%. The hybrid offsprings in another cluster had a closer genetic relationship with the paternal parent Egan No.1, consisting of 32 offsprings, accounting for 24.62%. The similarity coefficient between Egan No.1 and some of the offsprings was 0.905, while the similarity coefficient with the maternal parent Kiyomi was 0.81, indicating that these 32 offspring inherit more from the paternal lineage. The cluster analysis revealed that most hybrid offsprings had a closer genetic relationship with the maternal parent Kiyomi than with the paternal parent Egan No.1. The polyembryony analysis of the 130 hybrid offsprings showed that 38 plants (29.23%) exhibited only one band (no amplification of the MITE fragment), indicating they were monoembryonic offsprings. In contrast, 92 plants (70.77%) exhibited three bands with the amplification of the MITE fragment, indicating they were polyembryonic offspring. The statistical analysis revealed a gene segregation ratio of 1∶2.42, with polyembryonic offspring outnumbering monoembryonic ones in the hybrid population. Based on the chi-square test, the chi-square value of polyembryony trait was 22.430 8 with a p value of 2.178 56E-06 (<0.05), indicating that this trait may be regulated by multiple loci. Then, a statistical analysis of 44 fruit-bearing hybrid offspring of Kiyomi × Egan No.1 showed that 13 plants exhibited monoembryony, and 31 plants exhibited polyembryony, with a ratio of 1: 2.38. Among them, 84.09% of the monoembryonic and polyembryonic traits results were consistent between the molecular marker detection results and the morphological observation results. [Conclusion] The specific primers CHR2-2/CHR8-3/CHR8-4 were identified and could be used for genetic relationship identification in the offsprings of other hybrid combinations with Kiyomi as the maternal parent. According to the molecular markers detection, the segregation ratio of monoembryonic and polyembryonic offsprings was 1∶2.42, which was further validated with morphological observation, the polyembryony molecular markers demonstrated an 84.09% detection success rate in the hybrid population of Kiyomi × Egan No.1.